2003
DOI: 10.1177/15353702-0322805-31
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 Gene Expression Attenuates Angiotensin II-Mediated DNA Damage in Endothelial Cells

Abstract: Heme oxygenase (HO) catalyzes the conversion of heme to biliverdin with the release of iron and carbon monoxide. HO-1 is inducible by inflammatory conditions, which cause oxidative stress in endothelial cells. Overexpression of human HO-1 in endothelial cells may have the potential to provide protection against a variety of agents that cause oxidative stress. We investigated the physiological significance of human HO-1 overexpression using a retroviral vector on attenuation of angiotensin II (Ang II)-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 38 publications
1
36
1
Order By: Relevance
“…19,43 Indeed, inhibition of HO by the addition of SnMP or in cells underexpressing HO-1 resulted in increased cellular heme and decreased generation of the antioxidant, bilirubin, and oxidative stress. 13, 41 Mazza et al 44 have shown that a decrease in HO-1 proteins increased DNA degradation. Thus, HO-1 expression could have a major influence on the biological effect of oxidant stress.…”
Section: Discussionmentioning
confidence: 99%
“…19,43 Indeed, inhibition of HO by the addition of SnMP or in cells underexpressing HO-1 resulted in increased cellular heme and decreased generation of the antioxidant, bilirubin, and oxidative stress. 13, 41 Mazza et al 44 have shown that a decrease in HO-1 proteins increased DNA degradation. Thus, HO-1 expression could have a major influence on the biological effect of oxidant stress.…”
Section: Discussionmentioning
confidence: 99%
“…Bilirubin, in low concentrations, scavenges ROS in vitro, reduces oxidant-induced cellular injury, and attenuates oxidative stress in vivo (34,141,142,183). The antioxidant and cytoprotective effects of bilirubin in attenuating ANG II-mediated DNA damage and cell death have been described (116). Recently, increased expression of HO-1 resulting in elevated levels of biliverdin/bilirubin has been shown to preserve vascular integrity and prevent EC death and sloughing (178), thus enhancing vascular repairs in diabetic rats (12,196).…”
Section: Bilirubin and Oxidative Stressmentioning
confidence: 99%
“…These include its substrate, heme (9, 10); oxidative stress (11,12); the signaling proteins nerve growth factor, tumor necrosis factor-␣, interleukin-1␤, and interferon-␥ (13-15); and phenolic compounds such as curcumin and caffeic acid (16). Many reports have demonstrated the potent antioxidant activity of the heme-derived metabolites generated by HO-1 catalysis (biliverdin and bilirubin) and the cytoprotective actions of carbon monoxide on vascular endothelium and nerve cells (17)(18)(19)(20). Moreover, both HO-1-deficient mice (21) and a human case of genetic HO-1 deficiency (22) exhibit a serious impairment of iron metabolism, leading to liver and kidney oxidative damage and inflammation.…”
mentioning
confidence: 99%